MODEL OF COMPLEX SYSTEM FOR EVALUATION OF ENTERPRISE INNOVATIVE ACTIVITY - Z. N. Kozlovskaya; V. I. Kachanov (Наука и техника)
The paper contains an analysis of existing indices which are used for evaluation of the activity at the innovative enterprises. An original model of   a complex system for evaluation of the innovative enterprise activity is proposed in the paper.